2018
DOI: 10.3177/jnsv.64.48
|View full text |Cite
|
Sign up to set email alerts
|

Oral Glucose Tolerance and Tryptophan Metabolism in Non-Obese and Non-Insulin-Dependent Diabetic Goto–Kakizaki Rats Fed High-Tryptophan Diets

Abstract: SummaryWe investigated oral glucose tolerance and tryptophan (Trp) metabolism in non-obese and non-insulin-dependent diabetic Goto-Kakizaki (GK) rats fed high-Trp diets. Five-week-old male Wistar and GK rats were fed a 20% casein diet (control diet) or the same diet supplemented with 1%, 2%, 3%, or 5% Trp for 58 d. Oral glucose tolerance tests were performed on Days 14 and 28 of the experimental period. Urine as well as livers and blood were collected on the last day of the experiment. The glucose concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…and others found that the conversion ratio of tryptophan to nicotinamide was lower in streptozotocin‐ and alloxan‐induced diabetes, suggesting that de novo synthesis of NAD + from tryptophan appears to be impaired. This phenomenon was not observed in a type 2 diabetes model; Goto‐Kakizaki rats 104 .…”
Section: Summary Of the Plausible Mechanisms Of Dysregulation Of Nad+mentioning
confidence: 90%
“…and others found that the conversion ratio of tryptophan to nicotinamide was lower in streptozotocin‐ and alloxan‐induced diabetes, suggesting that de novo synthesis of NAD + from tryptophan appears to be impaired. This phenomenon was not observed in a type 2 diabetes model; Goto‐Kakizaki rats 104 .…”
Section: Summary Of the Plausible Mechanisms Of Dysregulation Of Nad+mentioning
confidence: 90%
“…Alteration of dietary TRP is often used as a non-invasive method to manipulate the TRP levels of the body, thereby affecting 5-HT neurotransmission in the CNS ( 39 ). HTD has been applied in the treatment of fatty liver disease ( 40 ), diabetes ( 41 ), Alzheimer's disease ( 42 ), and so on, which indicates that HTD may be safe and feasible as an adjunctive therapy. Our study is the first to demonstrate that HTD is an effective diet intervention in preventing SUDEP in DBA/1 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Alteration of dietary TRP is often used as a noninvasive method to manipulate the TRP levels of the body, thereby affecting 5-HT neurotransmission in the CNS [37]. HTD has been applied in the treatment of fatty liver disease [38], diabetes [39], Alzheimer's disease [40] and so on, which indicates that HTD is safe and feasible as an adjunctive therapy. Our study is the rst to demonstrate that HTD is an effective diet intervention in preventing SUDEP in DBA/1 mice.…”
Section: Discussionmentioning
confidence: 99%